THE PENGARUH TEMAN SEBAYA TERHADAP PERILAKU VERBAL BULLYING SISWA DI MI NURUL IMAN SANGKANMULYA KUNINGAN - Ine Novitasari; Nurhayati, Tati; Anita Alfiani, Dwi (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
Abstract. Verbal bullying is a type of bullying carried out through speech by someone and can be detected by the sense of hearing. This study was conducted with the aim of identifying the extent to which peer influence affects verbal bullying behavior among fifth-grade students at MI Nurul Iman Sangkanmulya Kuningan. The approach used was a quantitative approach with an ex post facto method. Data collection techniques included observation, questionnaires, and documentation, with a sample consisting of 27 fifth-grade students at MI Nurul Iman Sangkanmulya Kuningan, comprising 11 male and 16 female students. The data analysis in this study included normality tests, linearity tests, simple linear regression tests, t-tests, and determination coefficient tests. The results showed a significant influence of peers on verbal bullying behavior among fifth-grade students at MI Nurul Iman Sangkanmulya Kuningan, as the hypothesis testing revealed a Sig value of 0.002, which is less than 0.05 (0.002 < 0.05) with a determination coefficient of 31.4%. Thus, this study concludes that peers have an influence on verbal bullying behavior at MI Nurul Iman Sangkanmulya Kuningan.